2021
DOI: 10.3390/curroncol28050316
|View full text |Cite
|
Sign up to set email alerts
|

Designing Inclusive HPV Cancer Vaccines and Increasing Uptake among Native Americans—A Cultural Perspective Review

Abstract: Despite a global and nationwide decrease, Native Americans continue to experience high rates of cancer morbidity and mortality. Vaccination is one approach to decrease cancer incidence such as the case of cervical cancer. However, the availability of vaccines does not guarantee uptake, as evident in the Coronavirus 2019 pandemic. Therefore, as we consider current and future cancer vaccines, there are certain considerations to be mindful of to increase uptake among Native Americans such as the incidence of dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…Discrimination has long been a barrier to health care for Racialized and Indigenous communities. 23 , 48 , 49 , 77 , 86 The significance of culturally appropriate health care is also a repeated theme for Indigenous Peoples for COVID-19 vaccines, 87 , 88 non-COVID vaccines, 72 , 89 , 90 and healthcare more generally. 21 , 36 , 91–95 Findings from our study and previous research suggest the barriers and facilitators identified in this study reflect power relations that will continue shaping vaccine access and intentions for years to come.…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination has long been a barrier to health care for Racialized and Indigenous communities. 23 , 48 , 49 , 77 , 86 The significance of culturally appropriate health care is also a repeated theme for Indigenous Peoples for COVID-19 vaccines, 87 , 88 non-COVID vaccines, 72 , 89 , 90 and healthcare more generally. 21 , 36 , 91–95 Findings from our study and previous research suggest the barriers and facilitators identified in this study reflect power relations that will continue shaping vaccine access and intentions for years to come.…”
Section: Discussionmentioning
confidence: 99%
“…First, by the time the study was funded, rates of vaccine uptake were high among tribal partner communities. Despite concerns from historical experiences of misconduct [8] and structural inequalities worsening the impact of COVID-19 on Native nations [8,20], AI/AN led the way in first-dose and full vaccination rates throughout the pandemic. Distinct distribution networks, encouraging and culturally attuned vaccine messaging, and a greater perceived risk are just a couple of explanations for why AI/AN communities may demonstrate such strong vaccine uptake [21].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, rapid sharing of misinformation via television, websites, and social medias, coupled with confirmation bias, can exacerbate vaccine hesitancy [5,6]. It is important to give credible health information and be transparent when communicating about the COVID-19 vaccines, and especially to AI/AN communities who were not sufficiently represented in vaccine trials [7] and remain cautious towards research [8].…”
Section: Introductionmentioning
confidence: 99%
“…103 , 104 Vaccine research in partnership with Indigenous communities has proven the efficacy of numerous products that are recommended for routine use (eg, the Haemophilus influenzae type b vaccine, pneumococcal conjugate vaccine, and rotavirus vaccine), 105 , 106 , 107 , 108 , 109 and vaccines have been powerful tools for the reduction of infectious diseases in Indigenous populations. 46 , 64 , 95 , 110 , 111 Although distrust of health care and health-care abandonment have resulted in reduced vaccine uptake in some Indigenous populations, community-informed, community-led initiatives to improve vaccine uptake can improve vaccine impact. 104 , 112 , 113 However, even the best vaccines cannot accomplish health equity for Indigenous peoples.…”
Section: Challenges and Successes In Reducing The Burden Of Infectiou...mentioning
confidence: 99%